Poster No. 020 Increasing transvalvular gradient related to effectiveness of endogenous fibrinolysis in patients with severe aortic stenosis. (21st October 2022) - Kanji, Rahim; Panoulas, Vasileios F; Duncan, Alison; Davies, Simon W; Luscher, Thomas F; Mirsadraee, Saeed S; Arachchillage, Deepa R J; Gorog, Diana A
Abstract: Background: Patients with severe aortic stenosis (AS) are at risk of both bleeding and thrombotic events. The high shear and flow rates across the stenotic aortic valve (AV) degrade von Willebrand factor high molecular weight multimers increasing bleeding risk, but can also lead to platelet activation. The overall effect on thrombotic and endogenous fibrinolytic status remains unclear. We aimed to assess the relationship between AS severity and thrombotic and fibrinolytic profile. Materials and methods: In a prospective, observational study, thrombotic and thrombolytic status was assessed in venous blood taken from patients with severe AS using the Global Thrombosis Test. This point-of-care technique measures the time for occlusive thrombus formation under high shear (OT), and the time for spontaneous lysis of the thrombus (LT). We related these parameters to indices of AS severity. Results and conclusions: Our cohort comprised of 86 patients (age 79 ± 9 years, 58% male), of whom 25% were on single and 28% on dual antiplatelet medication, 47% on no antithrombotic therapy, and 1% on oral anticoagulation. Lysis time was inversely related to AV peak (r = −0.242, P = 0.04) and mean (r = −0.286, P = 0.012) gradients. The severity of AS, by gradient or valve area, was not related to OT, although OT was inversely related to platelet count (r = −0.248, P = 0.029). Heterogeneity in antithrombotic medications may have masked a relationship between AS severity and OT. We report that increasing severity of AS is related to more effective endogenous fibrinolysis, which may contribute to the increased propensity to bleeding.